• 1,2(b+1,2)+(0,5-b)(b+0,5)-(b+1,3)(1,3-b) при b= - 5/6

Ответы 1

  • 1,2(b+1,2)+(0,5-b)(b+0,5)-(b+1,3)(1,3-b)=1,2b+1,44+(0,5-b)(0,5+b)-(1,3+b)(1,3-b)=1,2b+1,44+0,5b^2-b^2-(1,3^2-b^2)=1,2b+1,44+0,5^2-b^2-((13/10)^2-b^2)=1,2b+1,44+0,5^2-b^2-(13/10)^2+b^2=1,2b+36/25+(1/2)^2-169/100=1,2b+36/25+1/4-169/100=1,2b+0=1,2b1,2b=1,2*(-5/6)=-1
    • Автор:

      jetta
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years